1968
DOI: 10.1002/cber.19681010127
|View full text |Cite
|
Sign up to set email alerts
|

Beitrag zum Mechanismus der Kehrmannschen Phenoxazonsynthese

Abstract: Auf Grund kinetischer Untcrsuchuiigen wird versucht, den Bildungsmechanismus von 5H-Benzo[a]phenoxazon-(5) (4) naher zu beleuchten. -Bei der Reaktion zwischen o-Aminophenol (1) und 2-Hydroxy-naphthochinon-( 1.4) (2) entstehen 2-[2-Hydroxy-anilino]-naphthochinon-(1.4) (3) und 4. Fur diese Reaktion k t die Anwescnheit von Luftsauerstoff erfortlerlich; in inerter Atmosphare findet keine mefibare Umsetzung statt. Bei der Bildung in k h a n o l reagiert 3 nicht weiter. In Eisessig ist 3 gleichzeitig Zwischcnprodukt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1970
1970
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…HC1 is a reasonably strong electrolyte (Kd = 1.1 X 10_2), and tetrazoles behave as weak bases. The data give the upper limit of the autoprotolysis constant of formic acid as 2.2 X 10-7. Acetic acid (26,96,124, H9, 205,250), acetic anhydride (27,81,142,149,198,240,272), or mixtures of these substances (163, 169,278) 167,169,198,240,272) or indicator (96,149 interferometric (263) and thermometric (262) methods have been reported for the titration of metal acetates or nitrogen bases in acetic acid. A variety of quaternary ammonium salts have been titrated in acetic acid using either indicator (88) or potentiometric (167) methods.…”
Section: Hcio4 <=mentioning
confidence: 99%
See 2 more Smart Citations
“…HC1 is a reasonably strong electrolyte (Kd = 1.1 X 10_2), and tetrazoles behave as weak bases. The data give the upper limit of the autoprotolysis constant of formic acid as 2.2 X 10-7. Acetic acid (26,96,124, H9, 205,250), acetic anhydride (27,81,142,149,198,240,272), or mixtures of these substances (163, 169,278) 167,169,198,240,272) or indicator (96,149 interferometric (263) and thermometric (262) methods have been reported for the titration of metal acetates or nitrogen bases in acetic acid. A variety of quaternary ammonium salts have been titrated in acetic acid using either indicator (88) or potentiometric (167) methods.…”
Section: Hcio4 <=mentioning
confidence: 99%
“…A series of oxazines (250) and aminoanthraquinones (149) (6) where values of a and b are characteristic of the indicator.…”
Section: Hcio4 <=mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that the pH measured in all experiments was above 6.5, while the pK a of NIR [20] is between 6 and 7. It was found that at pH higher than 6.5 there is no change in emission intensity peak wavelength.…”
Section: Nir Solubilizationmentioning
confidence: 98%
“…Oxazines have been investigated as indicators to be used in the titration of weak bases in nitromethane and in chloroform-dioxane mixture (217).…”
mentioning
confidence: 99%